THE PORTRAIT OF WOMEN STEREOTYPING IN INDONESIA AS DEPICTED IN INDONESIAN TELEVISION COMMERCIALS - Sri Hariyatmi, Ulupi Sitoresmi (Widya Wacana: Jurnal Ilmiah, 2014)
This paper aims to identify the stereotyping of women role as depicted in Indonesian television commercials. A sample of 60 commercials featuring women in eight Indonesian local televisions was examined during the third and fourth week of July by using content code analysis. The findings indicates that the stereotyping of women role portrayed in Indonesian television commercials exist in some aspects. Women are depicted as users of products mostly household and personal care.They are mostly portrayed as nurturing mother as well as an ideal housewife. When depicted as professional career women, still they are occupied with domestic role as a good mother. Keywords: television commercials, role portrayals, women stereotypes